2022
DOI: 10.3390/pharmaceutics14061202
|View full text |Cite
|
Sign up to set email alerts
|

Development of Irinotecan Liposome Armed with Dual-Target Anti-Epidermal Growth Factor Receptor and Anti-Fibroblast Activation Protein-Specific Antibody for Pancreatic Cancer Treatment

Abstract: Pancreatic cancer is one of the most common causes of death in Taiwan. Previous studies have shown that more than 90% of pancreatic cancer cells presented epidermal growth factor receptor (EGFR) cell marker, and this marker is thought to be important as it is related to activation of cancer cell proliferation, angiogenesis, and cancer progression. Moreover, tumor-associated fibroblasts were involved in tumor proliferation and progression. In this study, we fabricated an anti-EGFR and anti-fibroblast activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In a recent study conducted by Lin et al, anti-EGFR and anti-FAP bispecific antibody-targeted liposomal irinotecan was developed to target pancreatic cancer cells and tumor fibroblasts [ 100 ]. The formulation elicited improved cellular uptake and anticancer efficacy in a human pancreatic tumor-bearing mouse model compared to untargeted liposomal irinotecan and the results showed that fibroblast activation protein can be targeted for drug delivery.…”
Section: Peculiarities Of Pancreatic Cancermentioning
confidence: 99%
“…In a recent study conducted by Lin et al, anti-EGFR and anti-FAP bispecific antibody-targeted liposomal irinotecan was developed to target pancreatic cancer cells and tumor fibroblasts [ 100 ]. The formulation elicited improved cellular uptake and anticancer efficacy in a human pancreatic tumor-bearing mouse model compared to untargeted liposomal irinotecan and the results showed that fibroblast activation protein can be targeted for drug delivery.…”
Section: Peculiarities Of Pancreatic Cancermentioning
confidence: 99%
“…Currently, nanoparticles conjugated to antibodies or peptides to deliver the siRNA to target cancer cells have been the goal of many researchers [ 118 ]. The transferrin receptor (TfR), folate receptor, and Arginine-Glycine-Aspartic ligands are several examples of cell surface target receptors used since several studies prove that they are highly expressed in various types of tumors [ 141 , 142 ].…”
Section: Nano-based Drug Delivery Systems For Pancreatic Cancer Treat...mentioning
confidence: 99%
“…The results also showed a similar release rate and a better cellular uptake efficacy of BS-LipoIRI when compared to LipoIRI alone. In vivo testing results also concluded that BS-LipoIRI inhibited cancer growth up to 46.2% when contrasting to the controls, showing the great promise of BS-LipoIRI as a possible novel treatment for pancreatic cancer ( Figure 5 ) [ 118 ].…”
Section: Nano-based Drug Delivery Systems For Pancreatic Cancer Treat...mentioning
confidence: 99%
See 2 more Smart Citations